PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS STRATEGI BELAJAR METAKOGNITIF UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PEWARISAN SIFAT MANUSIA - YASIR, MOCHAMMAD (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
Majority of students get difficulty in learning human characterictic inheritance matter. One of possible reason is student worksheet decrease make student for understanding about matter. Based on this problem objective of this research were to develop student worksheet principle metacognitive learn strategy and describe it feasibility theoretically and empirically to promoted student learn result in human characterictic inheritance matter. This was development research, which develop student worksheet principle metacognitive learn strategy that developed by 3-D model. The results of this research indicated that student worksheet principle metacognitive learn strategy was theoretically feasible for the learning process with the percentage’s 91% (category: very feasible) and empirically based on learn result indicator complete 99,31%. Key words: student worksheet principle metacognitive learn strategy,metacognitive, metacompre hension.